Fracture mode of glass plate subject to low-velocity impact: experimental investigation and finite element simulation - Tomohisa KOJIMA (The Japan Society of Mechanical Engineers, 2019)
An understanding of the impact response of glass plates is important to protect people from injury. We investigated the fracture mode of a float glass plate that fractured under a low-velocity impact and conducted a numerical simulation. First, an impact fracture experiment of a float glass plate was carried out using a dropping weight, and crack development in the thickness direction of the glass plate was observed by a shadowgraph method. Then the numerical simulation was conducted applying two types of material models to the float glass: the Johnson–Holmquist model and the elastic model with tensile pressure failure. The two models were used in a simulation and the results were compared with the experimental result. At an impact velocity of 4.43 m/s, which correspond to the deformation velocity of the glass plate of 6.1 m/s in deflection, simulation with the Johnson–Holmquist model could reproduce the strain response of the glass plate but it could not reproduce the fracture mode of the glass plate. This result implied the limitation of applying the damage model to low-velocity impact for simulating the fracture mode of a glass plate. In the material model with elastic as the constitutive law and tensile pressure failure as the failure model, the simulated fracture strength of the glass plate was the same as the experimental fracture strength, and the fracture mode showed characteristics of the bending fracture mode that was observed in the experiment, although the fracture initiation time of the glass plate was slightly delayed in the strain history. In the low-velocity impact where the influence of inertia was small, the glass plate response could be reproduced easily using the elastic model. The efficacy of the model was confirmed in the simulation result with several deformation velocities.